An analysis of English Department Students’ Accuracy and Originality in Paraphrasing Science Text - Dwi Megista Putri (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2020)
Getting valuable information when write papers, paraphrase is an useful process. This research was conducted with aims to find out the students skill in paraphrasing, the problems faced and the causes of the problems in paraphrasing. There were 16 participants in this study. The data were collected from paraphrasing test, interview and questionnaire. The finding of the data analysis showed 62.5% of the students‟ ability in paraphrasing qualified in unsatisfactory level. From the test, it was found that the students made mistake in changing the order of ideas, lack of understanding toward the criteria of a good paraphrasing and changing word as their problem in paraphrasing. Last, lack of vocabulary and understanding about paraphrasing included as the causes of the students’ problems in paraphrasing.